Why Public Sector Projects Fail or Succeed in Pakistan- A Model for Evaluating Impact of HR Management Practices on Project Success - Hussain, Muhammad Rizwan (International Journal of Engineering and Management Sciences, 2022)
Employees are the most important assets of an organization. As quality human resources become scarce, companies need to pay more heed to the satisfaction and motivation of their employees. If employees are motivated towards work, then it is likely to yield better results. This study will examine the role of Human resource management (HRM) practices upon New product development (NPD). NPD involves technical, marketing, and financial risks organizations undertake for developing new products and services. Effective project planning and control are valuable for decision-making. The analysis of the impact of HRM practices on NPD, project success, and organizational benefit is based on data collected using a cross-sectional design via a survey questionnaire. The questionnaire consisted of items related to HR practices, New product development, Project Success, and Organizational benefits adapted from previous studies. Respondents working in 10 large-scale public sector projects executed by National Database & Registration Authority, Pakistan were selected for the study. Therefore, the results of the study can be generalized to similar projects executed by the public sector in Pakistan. From the findings of data analysis, it has been concluded that there is a significant association between HR practices and project success, but no significant relationship has been established between new product development and organizational benefit. Therefore, it can be concluded that HR management practices have a significant impact on public sector project success in the case of Pakistan.